Upaya Pemberdayaan Remaja Tentang Kesehatan Reproduksi Dalam Seksual Pranikah Di Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang Tahun 2023 - Ika Damayanti Sipayung; Ridesman Ridesman; Marta Armita Silaban; Damayanty S; Hadisyah Hadisyah (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
Introduction: Adolescents who used to be strongly maintained by the family system, cultural customs and existing traditional values, have experienced erosion caused by rapid urbanization and industrialization, this was also followed by a media revolution that was open to a variety of lifestyles and career choices. These various things have resulted in an increase in the vulnerability of adolescents to various kinds of diseases, especially those related to sexual and reproductive health, including the increased threat of HIV/AIDS. Method: Empowering Adolescents about reproductive health in premarital sex. Results: Participants in this activity were 30 pregnant women in the village of Bangun Rejo. In its implementation, the objectives are explained about the dangers of reproductive health, Benefits: how to detect premarital sexual attitudes. Next, it explains how teenagers avoid premarital sex to avoid disrupting reproductive health. Conclusion: community service activities are carried out based on counseling. Service activities carried out for 3 months. The results of this Community Service regarding the danger signs of adolescent reproduction. This community service has been carried out from May-July 2023 to be precise for 3 months